EFL Undergraduate Students’ Perspectives on Lecturer’s Teaching Styles in Academic Reading - Wardani, Happy Kusuma; Faizah, Lailatul (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research explores students’ perspectives on their lecturers’ teaching styles in the Academic Reading Course. Utilizing a descriptive qualitative approach through questionnaires and interviews, this research identifies Formal Authority, Personal Model, Facilitator, and Delegator teaching styles employed by the lecturer. Notably, 27 second-year EFL students at Universitas Qomaruddin participated in this research. Through Miles and Huberman model which comprises data reduction, data display, and conclusion, the results showed that most students strongly preferred the Personal Model type, which focuses on examples and guidance in teaching methods that significantly enhance their engagement and learning effectiveness. Therefore, this research recommends integrating more diverse, interactive, and student-centered teaching strategies to improve comprehension in the Academic Reading Course